Al-Ḥudayyda sous occupation ottomane (1849-1918) - Patrice Chevalier (Revue des Mondes Musulmans et de la Méditerranée)
Little fishing harbor on the Red Sea coast, al-Ḥudayyda’s status and dimension progressively change with the arrival of the Ottoman army in 1839. The town is then chosen as one of the strategic points (military and political) of the Ottoman colonial system.Thanks to the various infrastructures set up by the Ottoman administration, but thanks also to the opening of Suez canal in 1869, al- Ḥudayyda slowly attracts a multiethnic and cosmopolitan population: a part of it having come for trading aims, another part just taking refuge in the town, the political context being quiet unsettled in the area. Having just a little hundred inhabitants originally, al- Ḥudayyda’s population grows to 42 000 people on the eve of World War I.Is the cohabitation under the Ottoman administration going to generate exchanges or borrowings between the various communities or not? Are the Ottomans going to manage the transcending of the many identity belongings in order to create an “Empire citizenship”, as it is planned in their ambitious reform programme? Will al- Ḥudayyda be endowed with a specific identity strong enough to make people of various communities identify themselves with the town? These are some of the questions which this article tries to answer.